Does corporate governance affect financial performance of firms? A large sample evidence from India. Issue 4 (5th August 2020) - Sehrawat, Neeraj K.; Singh, Sumanjeet; Kumar, Amit
Abstract: The study of corporate governance is gaining momentum as its compliance has been made mandatory and the number of corporate governance issues is on the rise. Global scandals in Enron, WorldCom, and so forth. along with the rising number of domestic cases of misgovernance such as Satyam, Tata v/s Mistry have further stimulated the interest of policy makers, investors, academicians and other stakeholders in India. A number of studies have investigated the relationship between corporate governance and performance but the results remain inconclusive. We examine the relationship in the Indian context on a sample of 2, 552 non‐financial firms. The firm performance is measured by ROA and Tobin's Q and corporate governance characteristics are measured by the strength of the board, shareholding by executives, independence of the members of the audit committee and dual positions held by CEO. The results of the panel data analysis on 15, 671 firm year (2010–2019) shows that the CG factors, namely, audit committee independence, board size and CEO duality do not impact firm performance whereas managerial ownership revealed positive impact on firm performance (ROA). Audit committee independence and CEO duality have no impact whereas board size and managerial ownership revealed positive impact on firm performance (Tobin's Q ).